Trichobilharzia regenti n. sp. (Schistosomatidae, Bilharziellinae), a new nasal schistosome from Europe - Horák, P; Kolárová, L; Dvorák, J (Parasite (Paris, France), 1998)
Members of the genus Trichobilharzia are parasitic in visceral or nasal body parts of their avian hosts. The examination of water snails in South Bohemia revealed a schistosome infection in Radix peregra snails. The experimental infection of ducklings (Anas platyrhynchos, Cairina moschata) confirmed that a new Trichobilharzia species--T. regenti n. sp.--was found. The adults, eggs and larvae (miracidia and cercariae) of the species were morphologically characterized. The adult occupy the nasal blood vessels where they lay the eggs; the miracidia hatch from the eggs directly in the tissue and leave the host during drinking/feeding of the infected birds.
Keywords: nosní dutina; kur domácí; Male; Chickens; Česká republika; prevalence; infekce červy třídy Trematoda; mužské pohlaví; hlemýždi; nemoci ptáků; Czech Republic; Nasal Cavity; Schistosomatidae; Animals; ženské pohlaví; kachny; zvířata; Bird Diseases; Prevalence; Snails; Trematode Infections; Female; Ducks